49‐3: Building a Predictive Model of Contrast Ratio of Folded Optic Lens Systems for Virtual Reality. Issue 1 (28th June 2022) - Hao, Bing; Wong, Timothy; Le, John; Aastuen, David; Kotz, Art; Rosen, David; McGrath, Kayla; Kent, Susan
Abstract : Polarized catadioptrics (i.e., folded optics, pancake lenses) offer increased resolution and reduced aberrations across a wider field‐of‐view, and in a smaller physical package than conventional refractive optics for virtual reality (VR) head‐mounted display applications. One of the major challenges with polarized catadioptrics is achieving a high contrast ratio. In this paper we will review data generated experimentally and through simulations that demonstrate the impact of key system attributes on contrast ratio. The parameters we explore include the quarter‐wave plate material selection, scattering in the optical components, and rotational alignment between the polarization sensitive components.